1994
DOI: 10.1007/bf00202834
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese patient with the Costello syndrome

Abstract: The Costello syndrome is characterized by dwarfism, unique cutaneous lesions, distinct facial gestalt, and mental retardation. We present a Japanese patient with the Costello syndrome. She showed high serum IgM level during the early infantile period. Nissen's fundplication was carried out to treat severe gastroesophageal reflux. Endocrinological investigations revealed a partial deficiency of growth hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…As Johnson et al [1998] note, many findings in CS point toward a metabolic basis for the condition, and it is interesting to speculate whether this metabolic abnormality may originate in the hypothalamic-pituitary axis. This hypothesis is supported by the reports of combined GH and cortisol deficiency in the patient of Yetkin et al [1998] (and strongly suspected in our patient), combined GH and thyroid hormone deficiency in the patient of Gripp et al [2000], the other reported cases of isolated GH deficiency [Okamoto et al, 1994;Schimke et al, 1996;Legault and Gagnon, 2002;Delrue et al, 2003]], and mention of elevated prolactin levels in one patient with CS [Johnson et al, 1998]. Lin et al [2002] speculated that GH therapy in CS patients may cause the progression of existing cardiac hypertrophy, or initiate hypertrophy in patients with an apparently normal myocardium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As Johnson et al [1998] note, many findings in CS point toward a metabolic basis for the condition, and it is interesting to speculate whether this metabolic abnormality may originate in the hypothalamic-pituitary axis. This hypothesis is supported by the reports of combined GH and cortisol deficiency in the patient of Yetkin et al [1998] (and strongly suspected in our patient), combined GH and thyroid hormone deficiency in the patient of Gripp et al [2000], the other reported cases of isolated GH deficiency [Okamoto et al, 1994;Schimke et al, 1996;Legault and Gagnon, 2002;Delrue et al, 2003]], and mention of elevated prolactin levels in one patient with CS [Johnson et al, 1998]. Lin et al [2002] speculated that GH therapy in CS patients may cause the progression of existing cardiac hypertrophy, or initiate hypertrophy in patients with an apparently normal myocardium.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been noted that patients with CS are at increased risk for the development of tumors [DeBaun, 2002;Gripp et al, 2002]. Further, a few reports describe endocrine abnormalities in some patients with CS, specifically of growth hormone (GH) [Okamoto et al, 1994;Schimke et al, 1996;Yetkin et al, 1998;Legault and Gagnon, 2002;Delrue et al, 2003] and glucose metabolism [Di Rocco et al, 1993;Johnson et al, 1998;Yetkin et al, 1998;Szalai et al, 1999;Gripp et al, 2000]. We describe a patient with CS, with partial GH deficiency and hypoglycemia.…”
Section: Introductionmentioning
confidence: 83%
“…Children diagnosed and treated for GH deficiency show good catch-up growth with final adult heights ranging between À1.5 and À0.7 SDS [Price and Ranke, 1994;Blethen et al, 1997]. Children with Costello syndrome exhibit severe growth failure; however, there are reports of only two cases in which GH secretion was assessed and found to be deficient [Okamoto et al, 1994;Legault et al, 2001]. One of these patients showed limited response to GH therapy [ Okamoto et al, 1994], while the other (reported in follow-up here) responded well to initial therapy [Legault et al, 2001] and continues to grow well after several years on therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently additional cases [Borochowitz et al, 1992;Di Rocco et al, 1993;Patton and Baraitser, 1993;Philip and Mancini, 1993;Say et al, 1993;Teebi and Shaabani, 1993;Zampino et al, 1993;Fryns et al, 1994;Davies and Hughes, 1994;Okamoto et al, 1994;Vila-Torres et al, 1994;Czeizel and Tìmà r, 1995;Umans et al, 1995;Torrelo et al, 1995;Johnson et al, 1998;Kerr et al, 1998;van Eeghen et al, 1999] with Costello syndrome have been reported (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…(Anal) patient 2 1.5 yrs (Anal) 17 mths, ganglioneuroblastoma Di Rocco et al, 1993 5 yrs 5 yrs (Nasal) Teebi and Shalabani, 1993 18 mths Say et al, 1993 6 mths (limbs) ? (Laryngeal) Okamoto et al, 1994 7 yrs Fryns et al, 1994 6 yrs (Perianal) 12 yrs (Nasal) Davies et al, 1994 10 yrs (Lower eyelid) Vila-Torres et al, 1994 6 yrs 7 yrs (Nasal, neck) Torrelo et al, 1995 Birth birth (Nasal, perioral) Suri et al, 1998?, vestibular schwannoma Johnson et al, 1998: patient 1 9 yrs (Nasal) patient 2 teens (Nasal, facial) patient 3 Kerr et al, 1998: patient 1 patient 2 2 yrs, embryonal rhabdomyosarcoma 3 yrs, embryonal rhabdomyosarcoma Our case 2 yrs 11 yrs (Gingival) 12 yrs, carcinoma (Bladder)…”
mentioning
confidence: 99%